PEMBUATAN MEDIA ONLINE SISTEM INFORMASI PROFIL CV. CAKRAWALA COMPUTER - Muhammad Hibrian; La Ode Muhammad Saidi (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Information provided to users or users are users who are connected to each other. The internet plays an important role in human development in this century. One of the contents of the internet is in the form of online media that presents individual and company data presented in the form of online news. This profile information system or website is made using the PHP programming language with the codeigniter 3 framework, the database uses MySQL. The purpose of making this website is to increase promotional media, update information and increase people's purchasing power for sales of Laptops and Computer Accessories in the Baubau City community in particular and in Indonesia in general. Making a website or profile information system in addition to carrying out a digital marketing strategy for company products can also increase buyer, customer or user confidence in knowing what products or services are available in a business. Company media to convey the brand to the public, Making a company profile information system can look professional.